Politicization of Social Assistance and Abuse of Public Authority in Local Elections: Safeguarding Democratic Integrity in Indonesia - Anderson, Kevin; Cornelis, Vieta Imelda; Borman, M.Syahrul; Marwiyah, Siti (As-Siyasi: Journal of Constitutional Law, 2026)
The politicization of social assistance ahead of elections shows an increase, with programs intended to protect vulnerable communities being transformed into instruments for mobilizing electoral support by incumbent regional heads. This study aims to analyze the formulation of criminal law regarding the politicization of social assistance as a form of abuse of power, identify regulatory weaknesses, and develop a more effective legal reform model. The research employs a juridical-empirical method with a socio-legal approach, examining legislation on elections, regional governance, and corruption, and combining it with empirical data from election monitoring reports, regional budget documents, and selected case studies. Data were collected through literature review and institutional document analysis, then processed using qualitative-descriptive techniques to compare legal norms (das sollen) with actual practices (das sein). The findings reveal that the politicization of social assistance operates through three main patterns: budget manipulation aligned with electoral cycles, personalization of public programs to build political image, and bureaucratic mobilization to influence voter behavior. These practices exploit regulatory gaps, particularly limited criminal provisions and fragmentation among administrative, electoral, and anti-corruption legal regimes. The study demonstrates that such practices constitute a deviation from the purpose of authority (detournement de pouvoir) and should be addressed as more than procedural violations. The implication of this research highlights the need for a specific criminal offense framework based on the misuse of public policy, supported by stronger sanctions, integrated oversight, and clearer legal standards to safeguard democratic integrity and the neutrality of social welfare policies.